A cross‐sectional study exploring obesity and pregnancy planning among women attending an antenatal clinic in Suva, Fiji. (3rd August 2020) - Mudaliar, Jyotishna; Nusair, Pushpa; McCudden, Lucy; Melville, Peter; Rouse, Ian; Black, Kirsten
Abstract : Background: Pregnancy planning enables maternal health optimisation which is particularly important for women who have obesity and are at increased risk of adverse perinatal outcomes. Aims: The prevalence of pregnancy planning and its relationship to body mass index (BMI) was investigated in a cohort of women attending antenatal clinics in the main referral hospital in Suva, Fiji. Materials and Methods: The questionnaire captured health and socio‐demographic data, anthropometry and asked about pregnancy planning. Results: Two thousand, two hundred and three pregnant women presenting for their first booking at the antenatal clinic were enrolled; 721 (37.4%) out of 1926 women with complete data reported they did not plan their pregnancy. A third of women ( n  = 633, 32.8%) had overweight and 805 (41.7%) had obesity. In multivariable analyses parity, employment status, marital status, and BMI were significantly associated with pregnancy planning. Compared to women of a healthy weight or underweight, women who have obesity were less likely to plan their pregnancy (adjusted odds ratio 0.742; 95% CI 0.569–0.967). Conclusion: Tackling the cycle of obesity will require attention to preconception care and optimising weight before pregnancy.